Sanksi Pidana Terhadap Pelaku Tindak Pidana Kebakaran Hutan Padang Savana - Ni Luh Putu Tristania; I Ketut Kasta Arya Wijaya; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2025)
Law is a reflection of human conscience, so it cannot be separated from the nature of the nation. The savanna forest is a forest located in an arid area or an area with a small amount of plants, mainly grasses and weeds. Forest fires are an increasingly common form of disturbance. The formulation of the problem to be discussed is How is the legal regulation of environmental crimes against savanna forest fires? How is the perpetrator's responsibility for the criminal act of savanna forest fires? This research uses the type of normative legal research, with library techniques. Based on the regulation of criminal acts contained in the Criminal Code (KUHP) regulated in article 188. Provisions regarding savanna forest fires are also found in Law No. 41 of 1999 concerning Forestry in Article 78 paragraph (5).